PERAN SISTEM INFORMASI MANAJEMEN RUMAH SAKIT DALAM MENINGKATKAN KEPUASAN PENGGUNA LAYANAN KESEHATAN - Anggi Indah Kararea; Assyifa Azzahra Salsabila, Nurliana Hasibuan, Sri Hajijah Purba (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2025)
Hospital Management Information Systems (SIMRS) play an important role in improving the quality of health services and user satisfaction. The background to this research is the increasing need for hospitals to provide fast, accurate and integrated services to meet patient expectations. This study aims to analyze the role of SIMRS in increasing health service user satisfaction through a literature review approach. The method used involves collecting and analyzing data from various relevant scientific journals, published within the last five years. The research results show that effective SIMRS implementation can improve hospital operational efficiency, patient data accuracy, and communication between units, which has a direct impact on increasing user satisfaction. Further discussion identified factors supporting the success of SIMRS, including staff training, management support, and the availability of adequate technological infrastructure. The conclusion of this study confirms that SIMRS is not only an administrative tool, but also strategic in achieving better health services and improving the overall patient experience. Optimal integration of information technology in hospitals is expected to be a priority in improving the health service system in the future.